Extracellular vesicles as a next-generation drug delivery platform - Herrmann, IK; Wood, MJA; Fuhrmann, G (Springer Nature, 2021)
Extracellular-vesicle-based cell-to-cell communication is conserved across all kingdoms of life. There is compelling evidence that extracellular vesicles are involved in major (patho)physiological processes, including cellular homoeostasis, infection propagation, cancer development and cardiovascular diseases. Various studies suggest that extracellular vesicles have several advantages over conventional synthetic carriers, opening new frontiers for modern drug delivery. Despite extensive research, clinical translation of extracellular-vesicle-based therapies remains challenging. Here, we discuss the uniqueness of extracellular vesicles along with critical design and development steps required to utilize their full potential as drug carriers, including loading methods, in-depth characterization and large-scale manufacturing. We compare the prospects of extracellular vesicles with those of the well established liposomes and provide guidelines to direct the process of developing vesicle-based drug delivery systems.